Genetic and epigenetic mutations affect the DNA binding capability of human ZFP57 in transient neonatal diabetes type 1. Issue 10 (13th March 2013) - Baglivo, Ilaria; Esposito, Sabrina; De Cesare, Lucia; Sparago, Angela; Anvar, Zahra; Riso, Vincenzo; Cammisa, Marco; Fattorusso, Roberto; Grimaldi, Giovanna; Riccio, Andrea; Pedone, Paolo V.
Abstract : In the mouse, ZFP57 contains three classical Cys2 His2 zinc finger domains (ZF) and recognizes the methylated TGC met CGC target sequence using the first and the second ZFs. In this study, we demonstrate that the human ZFP57 (hZFP57) containing six Cys2 His2 ZFs, binds the same methylated sequence through the third and the fourth ZFs, and identify the aminoacids critical for DNA interaction. In addition, we present evidences indicating that hZFP57 mutations and hypomethylation of the TNDM1 ICR both associated with Transient Neonatal Diabetes Mellitus type 1 result in loss of hZFP57 binding to the TNDM1 locus, likely causing PLAGL1 activation. Abstract : ► hZFP57 zinc finger 3 and 4 are sufficient for high affinity DNA binding. ► hZFP57 TNDM1 mutations (R248H and H277N) affect DNA binding. ► DNA sequences in the TNDM1 ICR show DNA methylation‐dependent binding to hZFP57. ► mZfp57 inactivation results in loss of DNA promoter methylation and Plagl1 activation.